THE USAGE OF MODERN TECHNOLOGIES IN EFL VOCABULARY CLASSES (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
The article discusses the usage of multimedia tools and modern technologies in EFL vocabulary classes and the role of multimedia tools in the development of the quality of the lessons. In the globalization era every sphere of life requires the use of modern technologies even education.